Preferensi generasi z terhadap saham, sukuk, dan reksadana pada pasar modal syariah di Indonesia - Fitri, Yona; Sari, Sari (AL-Muqayyad, 2025)
The development of the Islamic capital market in Indonesia is showing rapid growth, along with increasing public interest in investments that comply with Sharia principles. Generation Z, as a technologically savvy, productive age group that dominates the number of digital financial platform users, has great potential as new investors. This study aims to analyze Generation Z's preferences for investment instruments in the Islamic capital market, namely Islamic stocks, sukuk, and Islamic mutual funds. Using a descriptive qualitative research approach with semi-structured interviews, this study involved 10 active investor informants from Generation Z. The results show that Islamic mutual funds are the primary choice due to their ease of access and minimal risk, while Islamic stocks are chosen by those with more advanced knowledge. Islamic sukuk are preferred by investors seeking stable returns. This study contributes to the development of literacy strategies and innovations in Islamic financial products that are friendly to the younger generation. The limitations in the number of informants and the research area open opportunities for broader follow-up studies. Overall, this study shows that Generation Z's investment preferences in the Islamic capital market are influenced by a combination of factors such as ease of access, risk level, investment knowledge, and aspects of religiosity and digital literacy.